Analisis Yuridis Terhadap Penolakan Nafkah Madhiah Isteri Dan Anak - Mansari; Elidar Sari; Salman Abdul Muthalib (Hukum Keluarga Islam IAIN LANGSA, 2022)
The panel of judges rejected the demands for a wife and children's financial support in the decision Number 251/Pdt.G/2021/MS.Mbo. Whereas a living that is not given during the marriage becomes a debt for the husband who has the right to be demanded back by the wife. This study aims to analyze the reasons for the judge's refusal to support his wife and children and the legal consequences of the refusal. The author uses a normative juridical research method. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Data analysis was carried out qualitatively. The results showed that the judge's consideration of rejecting the demand for a living was because only one witness from the two people who were presented to the trial was able to state that the defendant had never provided a living for his wife or children. The principle regulated in the procedural law is unus testis nullus testis which means one witness is not a witness. Juridically, the refusal of a living was appropriate because the panel of judges had taken into account the provisions of Article 172 of the HIR which stipulates that witness statements must match each other.